Whole-genome sequence analysis of SFTS bunyavirus in Huzhou, China - Deshun Xu; Lei Ji; Xiaofang Wu; Liping Chen (PLoS ONE, 2025)
Severe fever with thrombocytopenia syndrome (SFTS), a tick-borne emerging infectious disease caused by SFTS virus (SFTSV), is a growing public health threat due to its high mortality rate. To understand the genomic characteristics of SFTSV samples isolated in Huzhou, China, the full-length genomes of Huzhou SFTSV isolates obtained between February 1, 2019 and December 30, 2023 were sequenced, and the gene loci, evolution, and sequence identity of the genome sequences were analyzed using MEGA. The complete genome sequences of seven SFTSV samples were obtained successfully. The full-length genome of each isolate was 11 490 bp in length, composed of a large (L) segment of 6368 bp, medium (M) segment of 3378 bp, and small (S) segment of 1744 bp. The SFTSV samples isolated in Huzhou belonged to multiple genotypes, but were mainly of type D. Each subtype showed nucleotide sequence and amino acid sequence identities of more than 93.67% and 97.18%, respectively, with the syngeneic human host reference strain and more than 93.67% and 97.76%, respectively, with the syngeneic tick-derived host reference strain. Nucleotide sequence analysis of SFTSV isolates from Huzhou showed mutations in genes on all three segments, with those on the M segment showing the highest mutation rate. The nucleotide variations were mainly base transversions. Further studies of the distribution of SFTSV genotypes, sites of nucleotide mutations, and amino acid variations are required.